Fraud in Seventh Day Adventist secondary school in central Zimbabwe conference - Sithole, Bridget (Midlands State University, 2017)
The study established the relationship between the Fraud Triangle and the increase of fraud. It was prompted by the increase of repeated fraud cases in Seventh Day Adventist Secondary Schools in Central Zimbabwe Conference. The study adopted a quantitative descriptive research design to establish the relationship between the Fraud Triangle and the increase of fraud cases in Seventh Day Adventist Secondary Schools in Central Zimbabwe Conference. The population study considered was all the (11) elven secondary schools in Central Zimbabwe Conference. The population size of the study was 42(forty-two) respondents and self administered questionnaires were used to collect data from the administrators and accounting staff. The study found out that there was a positive relationship between the Fraud Triangle and the increase of fraud cases in the Seventh Day Adventist Secondary Schools in Central Zimbabwe Conference. The significant levels were not so high but however all the three factors that constituted the Fraud Triangle of pressure, opportunity and rationalization existed. From the findings, it was recommended that the triangle be dismantled. The leg of the Fraud Triangle which management has control over is the opportunity factors to commit fraud. Management was recommended to tighten more the internal controls of the institutions to reduce fraud. It was also recommended that seminars should be held regularly for key workers in schools in order sensitize them on fraud and its consequences both to the employee and to the organization. Finally it was recommended, that the remuneration committee should review the salary and benefits of employee if they were reasonable.